An update on management of the patient presenting with non-ST-elevation acute coronary syndromes. Issue 3 (26th May 2016) - Kaliyadan, Antony G.; Savage, Michael P.; Ruggiero, Nicholas; Fischman, David L.
ABSTRACT: Over 780, 000 patients in the United States are diagnosed with an acute coronary syndrome (ACS) each year. As physicians, it is our responsibility to provide prompt workup, diagnosis and management of these patients. After identification of the patient with ACS and confirming there is not ST-segment elevation MI requiring immediate revascularization, physicians should pursue a work-up for non-ST-elevation acute coronary syndrome (NSTE-ACS). It is important to understand the latest best practice guidelines in the treatment and management of patients with NSTE-ACS who carry high rates of in-hospital mortality. Physicians must integrate the clinical history and examination, electrocardiogram and laboratory findings in order to properly diagnose an NSTE-ACS. Early treatment with guideline directed medical therapy is imperative even in the setting of an early invasive strategy with cardiac catheterization and percutaneous coronary intervention. The focus of this review is to discuss the appropriate strategies for evaluation and management of patients with NSTE-ACS based on the most recent ACC/AHA practice guidelines.